Pelatihan Pencatatan Keuangan Sederhana Bagi Siswa MAN 2 Parepare, Kota Parepare, Provinsi Sulawesi Selatan - Ridfan Rifadly Abadi; Siti Hajerah Hasyim; M. Ridwan Tikollah; Kartika Septiary Musa; Syahir Fadli (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
The low level of financial literacy and the consumptive behavioral patterns among Indonesian youth represent a critical challenge in preparing the younger generation to face the complexities of the modern economy. Therefore, training in basic financial record-keeping serves as a strategic step in enhancing students' financial literacy, particularly at the secondary education level. This community service activity aims to improve the understanding and provide practical skills to students of MAN 2 Parepare in simple financial record-keeping. The goal is to enable students to manage personal finances and school-based entrepreneurial activities in a more orderly and responsible manner. The implementation method involved several stages, including preparation, training execution, and evaluation. The results indicated an increase in students' understanding of basic accounting concepts, the importance of financial recording, and their ability to prepare simple financial statements. This training has contributed to fostering students’ administrative discipline and financial awareness from an early age, enhancing youth financial literacy, and equipping them with essential skills for future financial independence.